A Feasibility study on TOP Recyclers Inc. - Olvidado, Ingrid; Ponferrada, Regidor; Tan, Katheryn (Diliman, Quezon City College of Engineering, 2002)
The name of the enterprise is TOP Recyclers, Inc. The term TOP is a combination of the names of the families owning this private corporation, namely. Tan, Olvidado, and Ponferrada. Furthermore, the term connotes the quality of the company's product and that the company is a leader in the recycling industry. The product of the company is zinc sows from galvanizer's zinc dross through the process of recycling. TOP Recycler, Inc.'s facility is located in San Jose, Antipolo City. The company chose this site based on five factors: cost of land, space requirements, raw material source, labor, and environment. The site in Antipolo City was chosen out of 5 alternative sites because of appropriateness to the criteria set by the company. Recycling has not been quite popular in the Philippines. Although some are educated about recycling some materials, such as paper, there is little implementation because of the lack of facilities. TOP Recyclers, Inc. plans to change all of this by initially offering zinc recycling. In ten years, the company hopefully has expanded to manufacturing other zinc forms aside from zinc sows, and recycling other metals such as aluminum. The company aims to provide recycled metals at the same quality as those mined. Because of the lack of quarries in the Philippines, most metals are imported. Companies could have great savings by using recycled metals as input to their production because there is no freight cost and lower prices. This feasibility study focused on five aspects- market, technical, organizational, financial, and social profitability. The business venture must be feasible in all aspects for it to be feasible. All aspects were treated with equal consideration, although the lifeblood of this feasibility study was the technical study. A brief summary is given of the different aspects of the feasibility study. Zinc is mainly used by the galvanizing companies in the Philippines. The market data have shown that there is slowly an increasing trend of zinc importation and its end uses. The organizational buyers of the company (galvanizing companies) are willing to buy recycled zinc provided they are of the same quality as imported zinc. The study showed that by selling at least 150 tons of recycled zinc monthly, the company would be able to achieve 20% of the market share. TOP Recyclers, Inc. is not planning to answer the whole demand as it is limited by the supply of zinc dross. An appropriate marketing strategy, using P 1.6M for the marketing budget, was developed for this industrial product. Recycling makes use of waste or scrap. The materials used in producing recycled zinc are zinc dross (galvanizer's scrap), lead and aluminum. The process of extracting the zinc from the zinc dross is very simple with the use of the tilting rotary furnace. Suppliers for the materials, equipment, and tooling were carefully evaluated and selected. The maximum production of TOP Recyclers, Inc. is at 2736 tons per year with furnace rated utilization at 55.7%. 38 people run the recycling facility in two shifts for five days a week. Finally, the costs involved in setting up the business to the construction of the facility in Antipolo City were gathered. Investment expenditure is at around P55M and operating expenditures is at around P13.8M annually. TOP Recyclers, Inc. is formed as a corporation. The advantages of this type of business organization made the company decide to become a corporation. All items considered and assumptions made, the total project cost in establishing TOP Recyclers Inc. is approximately P79M, and for five years, the total project cost would amount to P160M. The initial capital required would be about P80M. This includes the acquisition on land, materials, equipment and the working capital for one year. Equity financing will be used to financed this need by using 800 stocks worth P100,000 each. Financials statements such as the income statement, cash flow, and the balance sheet were projected for five years for show whether the project is financially feasible. The uses of financial ratios were further used to justify the profitability of the project. The NPV for the project was positive and the IRR was calculated to be 45%, this proves that operating TOP Recyclers Inc. was indeed profitable. Furthermore, it produced acceptable results for the financial ratios. TOP Recyclers Inc was proved to be socially profitable in the country. Some of the benefits include the energy and natural resources saved, the decrease in dependence on mining and smelting of zinc, the economic contributions to the nation. Although there were disbenefits cited, the benefits outweigh the disbenefits therefore it was concluded that the project is socially profitable.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management.
Keywords: TOP Recyclers, Inc; Zinc industry and trade; Participatory monitoring and evaluation (Project management)